Lumefantrine attenuates Plasmodium falciparum artemisinin resistance during the early ring stage - Kümpornsin, K; Loesbanluechai, D; de Cozar, C; Kotanan, N; Chotivanich, K; White, NJ; Wilairat, P; Gomez-Lorenzo, MG; Gamo, FJ; Sanz, LM; Lee, MCS; Chookajorn, T (Elsevier, 2021)
Emerging artemisinin resistance in Plasmodium falciparum malaria has the potential to become a global public health crisis. In Southeast Asia, this phenomenon clinically manifests in the form of delayed parasite clearance following artemisinin treatment. Reduced artemisinin susceptibility is limited to the early ring stage window, which is sufficient to allow parasites to survive the short half-life of artemisinin exposure. A screen of known clinically-implemented antimalarial drugs was performed to identify a drug capable of enhancing the killing activity of artemisinins during this critical resistance window. As a result, lumefantrine was found to increase the killing activity of artemisinin against an artemisinin-resistant clinical isolate harboring the C580Y kelch13 mutation. Isobologram analysis revealed synergism during the early ring stage resistance window, when lumefantrine was combined with artemether, an artemisinin derivative clinically partnered with lumefantrine. These findings suggest that lumefantrine should be clinically explored as a partner drug in artemisinin-based combination therapies to control emerging artemisinin resistance.